Sistem Informasi Berbasis Web Pada Kantor Urusan Agama Di Tamansari Kabupaten Bogor - Suci Sri Utami Sutjipto; Ade Mulyana; Anton Sukamto; M. Alvy Eka Fauzi (LPPM IBI Kesatuan, 2021)
In this fast-paced era, the need for precise, fast, and accurate information is something that must be done. Effectiveness and efficiency should be carried out according to needs so that the information can be relevant to its users. Thus, the registration information system, which has been manual in agencies or organizations, can be changed to online with accurate and timely data. Likewise, the Tamansari Religious Affairs Office in Bogor Regency. The current marriage registration system at the Tamansari Bogor Regency Office of Religious Affairs is no longer in line with the current development. The current system does not use computers as data processing tools, the results are still not well structured. Especially for processing the data of the prospective bride and groom. In this system, what is processed is registration data, bridal data, guardian data, witness data, admin data, and other data. The problem that occurs at this time is that the processed data feels slow, the resulting report has to pass data collection several times. In the information system to fulfill this final project, we will explain how to design and build a web-based marriage registration information system. The tools used in designing this system are MySQL, Entity Relational Diagrams, and Data Flow Diagrams, while for data collection using observation, interviews, and literature study. Meanwhile, database application development tools use MySQL and the programming language uses PHP. From this application, the benefits of data processing of brides, guardians, witnesses, etc. will be automatically obtained. Reports can also help by showing what is needed to process data quickly and easily. Keyword: Sistem Informasi, PHP My Admin, MySQL, Website, Entity Relational Diagram dan Data Flow Diagram